2006
DOI: 10.1111/j.1745-459x.2006.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size in Consumer Test and Descriptive Analysis

Abstract: This article deals with sample size (n) estimation by computer simulation using the variance of consumer and in-house sensory tests. The current sample size used in descriptive analysis was also examined. The sample size ranging from 20 to 200 was used to detect a difference ranging from 0.0 to 1.0 on a 9-point hedonic scale. For the simulated consumer data, significant difference was first observed at a difference of 0.60 when n = 40. Increasing the difference to above 0.60, the first significance likewise ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 8 publications
3
41
0
2
Order By: Relevance
“…According to Moskowitz (1997), 40–50 panelists would be sufficient for sensory acceptability test. According to Gacula & Rutenbeck (2006), a sample size of 40–100 would be sufficient to detect a difference ( d ′) of above 0.6 based on the Thurstonian d ′ value for perceptible difference for overall liking measured on a 9‐point hedonic scale. According to Moskowitz (1994), forty‐five responses per formulation would provide dependable, reliable results that could be used to generate models relating sensory qualities and acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…According to Moskowitz (1997), 40–50 panelists would be sufficient for sensory acceptability test. According to Gacula & Rutenbeck (2006), a sample size of 40–100 would be sufficient to detect a difference ( d ′) of above 0.6 based on the Thurstonian d ′ value for perceptible difference for overall liking measured on a 9‐point hedonic scale. According to Moskowitz (1994), forty‐five responses per formulation would provide dependable, reliable results that could be used to generate models relating sensory qualities and acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…Their results confirmed that minimal training was required for some texture and flavor attributes, whereas extensive training was required to discriminate other attributes. If the specific nature of the product differences and number of panelists are known, specific panel target performance (standard deviation) can be computed and modeled (Gacula and Rutenbeck, 2006). Generally, this information is not known and the panel leader must rely on data analysis collected from preliminary training sessions to confirm panel performance.…”
Section: Mainstream Sensory Testsmentioning
confidence: 99%
“…To truly understand the impact of information conditions regarding sugar source on product liking for a subgroup who favors one type of sugar source over the other, a larger number of panelist is needed. Between 40 and 100 panelists is necessary for a consumer test to obtain an adequate power (Gacula and Rutenbeck ).…”
Section: Resultsmentioning
confidence: 99%